2009
DOI: 10.1243/09544054jem1576
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network modelling of Nd:YAG laser microdrilling on titanium nitride—alumina composite

Abstract: Selection of machining parameter combinations for obtaining optimum circularity at entry and exit and hole taper is a challenging task in laser microdrilling owing to the presence of a large number of process variables. There is no perfect combination of parameters that can simultaneously result in higher circularity at entry and exit and lower hole taper. The current paper attempts to develop a strategy for predicting machining parameter settings for the generation of the maximum circularity at entry and exit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…For multiobjective optimization of the process for minimum surface roughness and minimum volume error, Particle Swarm Optimization (PSO) technique was used and it was observed that the proposed model and optimization technique can predict the optimum parameters accurately. Similarly, Biswas et al [191] have also developed neural network model to optimize the geometric features of micro-drilled hole in TiN-Al 2 O 3 .…”
Section: Artificial Intelligence (Ai) Modelsmentioning
confidence: 99%
“…For multiobjective optimization of the process for minimum surface roughness and minimum volume error, Particle Swarm Optimization (PSO) technique was used and it was observed that the proposed model and optimization technique can predict the optimum parameters accurately. Similarly, Biswas et al [191] have also developed neural network model to optimize the geometric features of micro-drilled hole in TiN-Al 2 O 3 .…”
Section: Artificial Intelligence (Ai) Modelsmentioning
confidence: 99%
“…In the field of laser cutting, most of the time the optimal cutting conditions are determined using the Taguchi method (Prajapati et al, 2013) and by coupling response surface models (Sivarao et al, 2013) and ANNs models with different optimization and metaheuristic algorithms such as particle swarm optimization (Ciurana et al, 2009), genetic algorithm (GA) (Tsai et al, 2008), and simulated annealing (Chaki & Ghosal, 2011). The open literature reveals several research attempts based on ANNs such as for modeling and optimization of laser micromachining process (Ciurana et al, 2009;Biswas et al, 2010;Dhara et al, 2008;Dhupal et al, 2007), selection of optimal laser cutting parameters through integration of ANNs with GA (Tsai et al, 2008;Ghoreishi & Nakhjavani 2008), development of a prediction model through integration with the Taguchi method (Yang et al, 2012) and parametric modeling and optimization of lasox cutting (Chaki & Ghosal, 2011). The ANNs are the learning algorithms and mathematical models, which imitate the information processing capability of human brain and can be applied to non-linear and complex data, even if the data are imprecise and noisy (Raja et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In laser cutting, the material is melted or evaporated by focusing the laser beam on the workpiece surface and coaxial jet of an assist gas removes the evaporated and molten material from the affected zone. Laser cutting is a high energy-density process that works quickly on the complex shapes, and is applicable to almost any type of material, generates no mechanical stress on the workpiece, reduces waste, provides ecologically clean technology, and has the ability to do work in the micro range [1]. Compared with other conventional machining processes, laser cutting removes much less material, involves highly localized heat input to the workpiece, minimizes distortion, and offers no tool wear [2].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,12,13,14,15]. The multi-objective optimization is done by combining the multiple objectives into single objectives through the use of weights or utility function.…”
Section: Introductionmentioning
confidence: 99%